The Word (Vāc) in the Cosmology and Soteriology of Kashmir Śaivism - Beinorius, Audrius (Acta Orientalia Vilnensia, 2001)
The article deals with the meaning of the Divine Word in the agamic Kashmiri Śaiva tradition. At first, making a brief overwiev of the history of the sacred word in Indian culture, attention is drawn to the fact, that the function of word and oral language as an agent of transformation from the human realm to the divine has been perennial concern of Indian theological speculation, since language in Hinduism is nearly always identified with both human consciousness and the divine cosmos. It has been pointed out, that an elaborate mysticism of the word found in the Śaiva Tantras has Vedic precendents and presupposes the philosophy of Bhartrhari. Tantra has the assumption that man and the universe correspond as microcosm and macrocosm and that both are subject to the mysterious power of words and letters. The Tantric Kashmiri tradition, while building upon the Śaiva-Āgamas and Grammarian tradition, formulates its own unique rational theology of traidic monism and of complex verbal cosmology, wherein sacred Verbum is fundamental to both the creation of the universe and to the reintegration of the soul into the cosmos. The climax of a hermeneutics of synthesis and the sacred word exegesis is represented in Abhinavagupta’s works. Abhinavagupta’s subtle speculation on the Word extends from its mystical dimension to the intricacies of Sanskrit alphabet and linguistic speculation, from psychological subtleties to philosophical reasoning.